Comparisonal Of Treatment Length And Laboratory Examination Comorbid And Non-Combid Disease On Covid 19 Patients At Hospital Royal Prima - Nanda Terin Ibrena Sembiring; Tan Suyono; Sri Lestari Nasution (CV. Inara, 2022)
Covid-19 is an infectious disease caused by a new type of coronavirus with symptoms of acute respiratory distress such as fever, cough, and shortness of breath. The type of research is comparative research with secondary data collection of as many as 280 comorbid patients and 280 non-comorbid patients in the month of august 2021 – January 2022. Data were analyzed univariately, bivariate with test Mann Withney. The results of this study are: Based on the mean length of stay for comorbid patients was 12.22 higher than that of non-comorbid patients, which was 5.28. The results of the laboratory examination of leukocytes in comorbid patients were higher at 13.17 than in non-comorbid patients, namely 10.07. In contrast, platelets were smaller, namely 268.87 than non-comorbid patients, namely 278.91. Neutrophils in comorbid patients were 76.28 higher than non-comorbid patients, namely 61.13. The lymphocyte of comorbid patients was 13.28 smaller than that of non-comorbid patients, which was 25.93. The D-dimer of comorbid patients was not too much different, namely 1259.85 than that of non-comorbid patients, namely 557.16. The conclusion in this study is that there is a significant difference between length of stay and laboratory tests (leukocytes, platelets, neutrophils, lymphocytes, D-dimer) for comorbid and non-comorbid diseases in Covid-19 patients at Royal Prima Hospital Medan.